2002
DOI: 10.1590/s0102-37722002000200004
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade comportamental em humanos: efeitos de regras e contingências

Abstract: Dois experimentos investigaram, com estudantes universitários, a variabilidade aprendida. No Experimento 1, quatro grupos (n = 5) foram submetidos a dois esquemas de reforçamento para seqüências de respostas de pressão às teclas P e Q do computador. Para o grupo Variabilidade (VAR) o reforçamento era dependente do alto grau de variação entre as seqüências, e para o grupo Acoplado (ACO) o reforçamento independia dessa variabilidade. Foram manipuladas a ordem de apresentação dessas contingências e o intervalo en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
11

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
1
0
11
Order By: Relevance
“…How might discrimination of one's own level of variability influence one's ability to modify such levels, and do influences that obscure discriminations therefore affect ability to change (see, e.g., van der Meer, van der Weel, & Lee, 1995)? Hunziker et al (2002) report that, although variability was successfully reinforced, their human subjects could not correctly describe the contingencies of reinforcement, a finding similar to those of informal observations in other studies (e.g., Neuringer, Deiss, & Imig, 2000), but whether subjects could discriminate variability levels rather than contingencies was not studied.…”
Section: Related Areassupporting
confidence: 61%
See 1 more Smart Citation
“…How might discrimination of one's own level of variability influence one's ability to modify such levels, and do influences that obscure discriminations therefore affect ability to change (see, e.g., van der Meer, van der Weel, & Lee, 1995)? Hunziker et al (2002) report that, although variability was successfully reinforced, their human subjects could not correctly describe the contingencies of reinforcement, a finding similar to those of informal observations in other studies (e.g., Neuringer, Deiss, & Imig, 2000), but whether subjects could discriminate variability levels rather than contingencies was not studied.…”
Section: Related Areassupporting
confidence: 61%
“…Hunziker, Lee, Ferreira, da Silva, and Caramori (2002) showed that, for human subjects, if Var contingencies were experienced just prior to Yoke contingencies, levels of response variation during the Yoke phase were higher than they would have been if the Var contingencies had not been previously experienced. The time delay between Var and Yoke experiences mattered, with a long interval (3 months) producing only a small effect.…”
Section: Parametersmentioning
confidence: 98%
“…O comportamento é, portanto, analisado sobre dados de variância, desvio padrão ou desvio médio, cujos valores apontam diretamente os graus de dispersão ou de variação. Enquanto eqüiprobabilidade, estudase a distribuição dos valores apresentados ao longo do universo de possibilidades considerando-se que quanto mais eqüitativa a distribuição dos eventos maior o grau de variabilidade (como em Denney, 1995;Ferraro & Branch, 1968;Hunziker, Caramori, Silva & Barba, 1998;Hunziker, Saldana & Neuringer,1996;Machado 1989;Neuringer, 1986;1991;Page & Neuringer, 1985;Stokes, 1995). Geralmente se entende que essas relações ocorrem em graus, dentro de um continuum, sendo que eqüiprobabilidade representa o caso máximo de variabili-…”
Section: H L Hunziker E R Morenounclassified
“…Para isolar os efeitos desta intermitência, Page & Neuringer (1985, Experimento 5) propuseram a utilização de uma contingência de acoplamento onde a distribuição dos reforços é a mesma da obtida em Lag-n, porém sem a exigência de variação. Com a utilização desse procedimento, diversos estudos demonstraram altos índices de variação sob Lag-n e reduzida variação na fase de acoplamento, o que demonstrou o controle da variabilidade comportamental pelas consequências (Page & Neuringer, 1985;Machado, 1989;Barba, 1997;Hunziker, Caramori, Silva & Barba, 1998;Hunziker et al, 2002;Neuringer, 1992Neuringer, , 1993Barba & Hunziker, 2002;Yamada, 2012). Caldeira, 2009;Brilhante, 2010, Giolo, 2010.…”
Section: Figura 5 -Valores Médios Do íNdice U (E Desvio Padrão Indicunclassified